Process Efficiency Optimisation of Cascade LNG Process - Najibullah Khan, Nazreen Begum (Curtin University, 2018)
The aimed of this thesis is to optimise the Cascade LNG process efficiency of 5 MTPA production capacity. The cascade process was modelled and simulated in Aspen HYSYS version 7.2 using Peng Robinson equation of state. The optimisation of cascade process was carried out from operation and design perspectives. It focused on two main cycles which are propane and ethylene refrigeration cycles as they are the main energy consumers of this process.